The Standard of the Taste and the Taste Disagreements in Hume's Thoughts - ali salmani (حکمت و فلسفه, 2011)
Since Hume believes that beauty is pleasurable sentiment, he can not refer to the certain objective qualities for resolving aesthetical disputes. Hence, he introduces the common judgment of judges as the standard of the taste. Hume himself accept that in spite of efficiency of this standard, tow factors, namely different humors and different particular manners, lead to a kind of constricted relativism in the aesthetic judgment. A precise investigation will show that this standard can be successful in the simple and none-comparative situations. However, in the case of comparative judgments - when we speak about preferences of an artist in comparison to the other's ones - this standard can not be efficacious. If beauty is pleasurable sentiment, everybody accredit his sentiment and would not accept other's sentiment.